Effect of organics amendements andTrichodermaspp on Meloydogine spp management - Baños, Yoerlandy Santana; Concepción, Armando del Busto; Gonzales, Irisley Aguiar; Lazo, Ricardo Cruz; Morejón, Liudmila Palomino (Revista Brasileira de Agroecologia, 2010)
The root-knot nematodes (Meloidogyne spp.) constitute one of the most important plagues that affect the cultivation of vegetables due to the losses that it causes annually. With the objective of reducing the levels of infestation of Meloidogyne spp. in the tomato cultivation, the effect of hen-dung (2,4 kg/ha), molasses (10 l/ha) and Trichoderma spp. (9 kg/ha) was evaluated in the management of the plague,compared with a witness without treating. As results it decreased the infestación of Meloidogyne spp. significantly in the cultivation 80 days after the transplant, being more effective T. viride and T. harzianum, with reductions of 2,0 and 1,94 degree, respectively. The application of T. viride, T. harzianum, molasses and hen-dung, showed a stimulating effect on the morfological, physiologic and productive parameters of the tomato cultivation, reaching yields of 47.05, 46.56, 38.75 and 34.99 t/ha, respectively, with significant differences on the witness. The evaluated alternatives allow to obtain increments in the production superiors of 30 %, justifying the application expenses.